Pengembangan Profesionalisme Guru Melalui In House Training - Baharuddin Baharuddin; Rabial Kanada (El-Idare, 2017)
The development of teacher professionalism is in the spotlight of today's world. This is due to the changing paradigm of education as a consequence of the development of the times and challenges of education. This paper aims to provide an overview and understanding of the importance of changing old patterns in developing a teacher's professional. Monotonous and centralistic coaching and training is no longer relevant to use for the present. One of the new methods that deserve to be practiced as a form of teacher professional development is through in-house training. A method that puts forward collaborative, contextual and constructivist approaches so that the value of its benefits is more clearly felt by teachers.